2007
DOI: 10.1063/1.2817623
|View full text |Cite
|
Sign up to set email alerts
|

Quantum conductance in single- and double-wall carbon nanotube networks

Abstract: The electrical conductance of single- and double-wall carbon nanotube systems was measured by a mechanically controllable break-junction technique using freestanding nanotubes not subject to any chemical modification. For metallic single-wall carbon nanotubes, two channels with transmission coefficient of 0.88 contribute to ballistic electronic transport at room temperature. In double-wall carbon nanotubes, one metallic channel contributes to ballistic electronic transport and additional field- and temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 40 publications
3
15
0
Order By: Relevance
“…18 The work of Poncharal et al 4 reported values of 0.6G 0 and 0.8G 0 as the most frequently observed noninteger values of the conductance from protruding bundles. Recently, we have observed similar results in pristine, freestanding SWNT and DWNT systems at room temperature, 8 and concluded that SWNTs are two-channel ballistic conductors with a transmission coefficient of 0.88. We have also suggested these DWNTs, produced by the coalescence method, are approximately one-channel ballistic conductors with additional field-and temperature-dependent twochannel contributions.…”
Section: Introductionsupporting
confidence: 57%
See 4 more Smart Citations
“…18 The work of Poncharal et al 4 reported values of 0.6G 0 and 0.8G 0 as the most frequently observed noninteger values of the conductance from protruding bundles. Recently, we have observed similar results in pristine, freestanding SWNT and DWNT systems at room temperature, 8 and concluded that SWNTs are two-channel ballistic conductors with a transmission coefficient of 0.88. We have also suggested these DWNTs, produced by the coalescence method, are approximately one-channel ballistic conductors with additional field-and temperature-dependent twochannel contributions.…”
Section: Introductionsupporting
confidence: 57%
“…The aim is to elucidate interwall interaction effects on the transport properties in DWNTs. The dispersion in diameter and interwall separations for this CVD-grown DWNT sample is superior to that of DWNTs produced by the C 60 -SWNT coalescence method 14 used in our previous study 8 and is therefore closer to the ideal of a completely phase-pure DWNT sample.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations